REFLEKSI NILAI KEMANUSIAAN DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER DALAM KELAS PANCASILA 41 - Putra, Dzaky Wajendra Kusuma; Ratna Endang Widuatie; Anindya Florean Arkananta; Nasywa Kirana; Adrian Haris Maulana; Chelsea Amara Ariyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Indonesian literature plays an important role in instilling human values, particularly through works that address social issues and justice. Pramoedya Ananta Toer’s novel Bumi Manusia, set in the era of Dutch colonial rule in the East Indies, portrays human conflicts such as racial discrimination, legal injustice, and the oppression of indigenous people. This article analyzes the implementation of the value of